Successful conservative management of a superficial pediatric pseudoaneurysm - Jouseph Osama Barkho; Anthony K.C. Chan; Matthew Choi (Elsevier, 2018)
Purpose: (1) To report a case of successful non-operative management of a pediatric pseudoaneurysm in a patient with severe factor V deficiency. (2) To review the literature on pediatric pseudoaneurysms managed with a trial of conservative therapy. Methods: A review of the literature was conducted on OVID-Medline for case reports or series of pediatric pseudoaneurysms managed conservatively (observation or external compression). Only superficial, radiologically confirmed pseudoaneurysms managed conservatively were included. Demographic data, etiology, treatment modalities, success rates, and definitive management for cases where conservative management failed were examined. Results: Twelve case reports of 13 pseudoaneurysms met inclusion criteria. Including our case, the mean age was 7 years and the most common pseudoaneurysm etiology was iatrogenic (57%). Seventy-nine per cent (11/14) of pseudoaneurysms resolved with conservative management, and 21% (3/14) proceeded to surgery due to increasing size, bleeding, or pain. Of those pseudoaneurysms successfully treated conservatively, 18% (2/11) developed a complication. Five pseudoaneurysms occurred in patients with coagulopathies, all of which resolved conservatively. Conclusion: In stable, asymptomatic superficial pediatric pseudoaneurysms, a trial of conservative management and close follow-up is a reasonable option, even in patients with coagulopathies. Keywords: False aneurysm, Neonate, Conservative, Non-surgical, Hemophilia